Peran Guru dalam Pembelajaran Pendidikan Pancasila untuk Meningkatkan Karakter Siswa Kelas 1 SDIT Persada Bayat Klaten - Cindy Mitha Puspitasari; Putri Zudhah Ferryka; Isna Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to find out: (1) The role of Pancasila Education teachers in improving the character of grade I students at SDIT Persada (2) How teachers apply religious, disciplined, and responsible character values. This research is qualitative research through descriptive analysis methods. The primary data sources in the research are Pancasila Education teachers in class I and students of grade I SDIT Persada Bayat. Research instruments use observation, interviews, and documentation. This research uses data validity and credibility testing using triangulation. The data analysis techniques used in this study use Miles and Huberman analysis models consisting of data collection, data reduction, data presentation, and inference. The results of research conducted at SDIT Persada Bayat can show that: (1) Teachers act as educators, teachers, learning resources, supervisors, demonstrators, motivators and evaluators in improving the character of students. Where the role of the teacher is very influential on improving the character of students in the learning process and outside the learning process. (2) Religious values, discipline and responsibility are strongly emphasized in the school environment. This value must also be formed in the family environment, and in school continue what is already formed from home.